The immune checkpoint molecule VISTA regulates allergen-specific Th2-mediated immune responses. (15th December 2017) - Ohno, Tatsukuni; Zhang, Chenyang; Kondo, Yuta; Kang, Siwen; Furusawa, Emi; Tsuchiya, Kimitake; Miyazaki, Yasunari; Azuma, Miyuki
Abstract : VISTA inhibits allergic inflammation in asthma Abstract: V-domain immunoglobulin suppressor of T-cell activation (VISTA) is a novel immune checkpoint receptor and ligand that regulates T-cell activation. We investigated the functional involvement of VISTA in Th 2 cell-mediated immune responses using an ovalbumin (OVA)-induced allergic asthma model. Treatment with an anti-VISTA monoclonal antibody (mAb) during allergen sensitization increased the production of antibodies, including total IgE, OVA-specific IgG1 and IgG2a and allergen-specific IL-5 and IL-13; it also increased the expression of IL-13 by splenic CD4 + T cells. However, treatment with the anti-VISTA mAb during sensitization did not accelerate asthmatic responses, including airway hyper-responsiveness (AHR) or the number of eosinophils in bronchoalveolar lavage (BAL) fluid. In contrast, treatment with the anti-VISTA mAb during allergen challenge significantly augmented AHR and BAL fluid eosinophilia. This treatment also increased the production of IL-5 and IL-13 in BAL fluid and the expression of IL-13 by CD4 + T cells in draining lymph nodes. These results suggest that VISTA is involved in the regulation of Th 2 cell generation and Th 2 cell-mediated antibody production and regulates asthmatic responses, especially in the effector phase.